Case ascertainment of alcohol dependence in general population surveys: ‘gated’ versus ‘ungated’ approaches - Degenhardt, Louisa (Int J Methods Psychiatr Res, 2007)
Social role impairment and other forms of maladaptation are referenced explicitly in the case definitions for the drug use disorders within DSM‐IV‐TR, but there is continuing debate about whether and how to include these manifestations of ‘clinical significance’ in diagnostic criteria and assessment protocols. When a ‘gated’ approach (based on impairment or other maladaptation) has been taken during recent large scale psychiatric surveys with coverage of drug dependence (e.g. to reduce participant fatigue or burden), the net effect may include (a) a reduced number of identified cases, and (b) biases in the estimates of association linked to the occurrence of drug dependence. In this report focused on alcohol dependence, we probe these issues, making use of data from the cross‐sectional US National Epidemiologic Survey on Alcohol and Related Conditions (NESARC), a household survey with 44,093 adult participants. NESARC alcohol dependence assessments were ‘ungated’, but allowed simulation of a ‘gated’ approach; the end result was a robust decrement in the estimated prevalence of this condition. Nonetheless, patterns of association linking suspected background characteristics to prevalence of alcohol dependence were not appreciably different when the gated and ungated estimates were contrasted. In summary, there are reasons to take the ungated approach in detailed research on alcohol use and dependence. Nevertheless, in panoramic mental health surveys, the inefficiency of an ungated approach must be balanced against the anticipated yield of cases who have experienced alcohol dependence without alcohol related social role impairments or other maladaptation, particularly when the dependence syndromes without these consequences are sometimes thought to lack clinical significance. Copyright © 2007 John Wiley & Sons, Ltd.